Safety and Feasibility of Tele-Supervised Home-Based Transcranial Direct Current Stimulation for Major Depressive Disorder - Cappon, Davide; den Boer, Tim; Jordan, Caleb; Yu, Wanting; Lo, Alexander; LaGanke, Nicole; Biagi, Maria Chiara; Skorupinski, Pawel; Ruffini, Giulio; Morales, Oscar; Metzger, Eran; Manor, Bradley; et al. (Frontiers in Aging Neuroscience, 2022)
Major depressive disorder (MDD) is a worldwide cause of disability in older age, especially during the covid pandemic. Transcranial Direct Current Stimulation (tDCS) is a non-invasive neuromodulation technique that has shown encouraging efficacy for treatment of depression. Here, we investigate the feasibility of an innovative protocol where tDCS is administered within the homes of older adults with MDD with the help of a study companion (I.e. caregiver). We further analyze the feasibility of a remotely-hosted training program that provides the knowledge and skills to administer tDCS at home, without requiring them to visit the lab. We also employed a newly developed multi-channel tDCS system with real-time monitoring designed to guarantee the safety and efficacy of home-based tDCS. Participants underwent a total of 37 home-based tDCS sessions distributed over 12 weeks. The protocol consisted of three phases each lasting four weeks: an acute phase, containing 28 home-based tDCS sessions, a taper phase containing 9 home-based tDCS sessions, and a follow up phase, with no stimulation sessions. We found that the home-based, remotely-supervised, study companion administered, multi-channel tDCS protocol for older adults with MDD was feasible and safe. Further, the study introduces a novel training program for remote instruction of study companions in the administration of tDCS. Future research is required to determine the translatability of these findings to a larger sample.